PEMBERDAYAAN SISWA BERKEBUTUHAN KHUSUS MELALUI KETERAMPILAN UNTUK MELATIH KEMANDIRIAN DI SLB PSM TAKERAN – MAGETAN - Mulyati, Tatik; Utami, Saraswati Budi; Susilo, Hendro (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Students at the Extra Ordinary School of Pesantren Sabilil Muttaqien (SLB PSM) Takeran Magetan Regency are dominated by students with special needs with mental disabilities. Paying attention to the fact that the student population is quite large, it is necessary to be concerned with creating empowerment programs to encourage community involvement in order to help students with special needs in order to achieve independence. In general, students have a background of poor socio-economic conditions and need help from other parties to improve their living conditions. On the other hand, the empowerment program from the local government has not been able to reach all existing students, so they find it difficult to increase resources. The purpose of community service to students at SLB PSM is to help students with special needs in improving skills and welfare, with the following objectives: 1. Facilitating the availability of materials, equipment and facilities needed as business capital; 2. Skills training and production of goods that can be made by students with special needs; 3. Ensuring the sustainability of businesses that have been initiated and developed; 4; Realizing business independence for students with special needs. Activities are carried out by pioneering and making various types of skills by utilizing ciprat batik cloths so that they can have artistic value, are economical and market-oriented, so that they can earn income to meet their daily needs. Abstrak. Siswa di Sekolah Luar Biasa Pesantren Sabilil Muttaqien (SLB PSM) Takeran Kabupaten Magetan banyak didominasi oleh siswa berkebutuhan khusus tuna grahita. Memerhatikan fakta bahwa populasi siswa tersebut cukup banyak, perlu kepedulian dengan membuat program pemberdayaan unuk mendorong keterlibatan masyarakat agar membantu siswa berkebutuhan khusus agar bisa mewujudkan kemandirian. Secara umum, para siswa memiliki latar belakang kondisi sosial ekonomi miskin dan membutuhkan bantuan dari pihak lain untuk meningkatkan kondisi kehidupannya. Di sisi lain, program pemberdayaan dari pemerintah daerah juga belum mampu menjangkau seluruh siswa yang ada, sehingga mereka kesulitan untuk meningkatkan sumber daya. Tujuan pengabdian masyarakat pada siswa di SLB PSM adalah membantu siswa berkebutuhan khusus dalam meningkatkan keterampilan dan kesejahteraan, dengan tujuan: 1. Memfasilitasi ketersediaan bahan, peralatan serta sarana yang dibutuhkan sebagai modal usaha; 2. Pelatihan keterampilan dan produksi barang yang mampu dibuat oleh siswa berkebutuhan khusus; 3. Menjamin keberlanjutan usaha yang telah dirintis dan dikembangkan; 4; Mewujudkan kemandirian usaha bagi siswa berkebutuhan khusus. Kegiatan dilaksanakan dengan cara merintis dan membuat aneka jenis keterampilan dengan memanfaatkan perca kain batik ciprat agar bisa memiliki nilai seni, ekonomis dan berorientasi pasar, sehingga memeroleh pendapatan guna memenuhi kebutuhan hidupnya.